IMPLEMENTATION OF INTEGRATED MARKETING COMMUNICATION BASED ON OMNICHANNEL MARKETING IN THE JUNIQUE MARKETING PROGRAM - Safitri, Niken; Marsasi, Endy Gunanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Still, the existence of Covid-19 affects all layers of elements, especially for automotive companies, both two-wheeled and four-wheeled. National motorcycle sales are known to be affected quite hard by Covid-19. The distribution and sales of motorcycles experienced a decline in motorcycles sold throughout Indonesia only reaching 123,782 units, or a decrease of 78 percent compared to the previous month. People's purchasing power at the time weakened due to declining incomes. Therefore, marketing strategy plays an important role in maintaining business growth in the long term. This research aims to evaluate and improve the effectiveness of existing programs within the company. The research methods used are qualitative, including direct observation, interviews, documentation collection, and primary and secondary data. The results of this research are expected to help companies in innovating and overcome weaknesses. Astra Motor Purworejo can implement Integrated marketing communication through the concept of omnichannel marketing. To optimize the use of digital marketing.